Influence of the Mediterranean diet on seminal quality—a systematic review - Piera-Jordan, Clara Ángela; Prieto Huecas, Laura; Serrano De La Cruz Delgado, Verónica; Zaragoza Martí, Ana; García Velert, María Belén; Tordera Terrades, Cristina; Sánchez-SanSegundo, Miriam; Hurtado-Sánchez, José Antonio; Tuells, José; Martín Manchado, Laura (Frontiers in Nutrition, 2024)
Currently, there is a growing interest in the study of fertility because fertility-related problems affect up to 15% of the world’s population. The aim of this study was to determine the influence of the Mediterranean diet on seminal quality in men of reproductive age. For this purpose, a systematic review of the literature was carried out following the PRISMA method. Electronic searches were carried out in the international databases PubMed, Scopus, the Cochrane Library, and Web of Science. In total, 10 articles with 2032 men were included. As inclusion criteria, articles published between 2012 and 2022 were selected, including those that included men aged between 18 and 55 years. Nutritional status was assessed through weight, height, and BMI. Dietary habits were evaluated through different indexes and food frequency questionnaires, and finally, semen quality was evaluated by measuring sperm concentration and motility (progressive and non-progressive). In six (60%) of the included articles, a positive relationship between adherence to the Mediterranean diet and semen quality was demonstrated; in two (20%) of the articles, no association was found; and finally, in two (20%) of the included articles, the relationship between dietary patterns typical of DM and semen quality was evaluated. Dietary habits influence semen quality. Adherence to the Mediterranean diet can improve male reproductive health, as it is a diet with antioxidant and anti-inflammatory effects. This is the first systematic review about the influence of the Mediterranean diet on semen quality, and the results are positive. These findings may allow us to provide better advice to our patients and to establish interventions with the aim of improving the results of assisted reproduction techniques.